The influence of entrepreneur’s innovation and entrepreneurship on modern art teaching model - Zhang, Xuan; Wang, Lin (Frontiers in Psychology, 2022)
It is necessary to explore the significance of innovation and entrepreneurship to Chinese art education. The organization and operation mechanism of innovation and entrepreneurship education (IEE) is studied according to the current situation of IEE in Chinese art colleges and universities. The IEE system of art colleges and universities is optimized, and a new teaching model of IEE with the characteristics is explored. In addition, the research methods are theoretical analysis, comparative analysis, and empirical analysis. The objects are students from some domestic art academies. The influence of innovation and entrepreneurship on the modern art teaching model is explored. It mainly investigates the awareness and needs of college students' innovation and entrepreneurship, the professional knowledge of students participating in related activities, the transformation of achievements, and the system and management of IEE. Based on this, a new teaching model of innovation and entrepreneurship is proposed. The six dimensions of creativity, initiative, interest, ideation, independence, and concentration of students in this model are evaluated. The results show that the spirit of innovation and entrepreneurship has a significant role in improving the contemporary art education model on these six dimensions. It is found that this spirit is vital for the development of contemporary art education. In art education, the application of entrepreneurship improves students’ thinking and practical ability. And this spirit is an important part of the construction of contemporary art education.